SPEAKING SKILLS AS A TOOL FOR CRITICAL THINKING DEVELOPMENT - Балжанова, А.М.; Акимова, З. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
Speaking as one of the basic skills can help us to express our own ideas and thoughts; therefore on the basis of increasing students’ speaking skills we open them new ways for their critical thinking and self-development. Critical thinking is a developed complex set of skills and features which takes years to acquire. This article aims to highlight peculiarities of critical thinking development and to determine the feasibility of increasing students` critical thinking degree through developing their speaking skills at English lessons.
Keywords: education; critical thinking; speaking skills; foreign language